"It truly does get better": Young sexual minority men's resilient responses to sexual minority stress. Issue 3 (2nd July 2020) - Harkness, Audrey; Rogers, Brooke G.; Albright, Christopher; Mendez, Noelle A.; Safren, Steven A.; Pachankis, John E.
Abstract: Due to minority stress, sexual minority men experience mental health disparities. Sexual minority men who engaged in cognitive-behavioral therapy to address the minority stress underlying their distress completed an exercise eliciting their own resilience. This exercise involved writing an advice letter to a hypothetical peer about coping with minority stress. Qualitative analysis of these letters yielded 18 codes grouped into three categories reflecting resilience to minority stress. Categories included (1) cultivating internal affirmation strategies, (2) building supportive relationships and community, and (3) using cognitive and behavioral skills to cope with minority stress. Findings highlight this population's resilience and suggest building resilience through treatment.